2016
DOI: 10.14202/vetworld.2016.1392-1399
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in role of chromium and its antioxidant combinations in poultry nutrition: A review

Abstract: Poultry is reared in open side houses in most of the tropical countries, which results in huge temperature variation in shed causing stress resulting in increased demand of antioxidant supplementation. Since cooling of poultry houses or environment control is very expensive, thus methods focused on nutritional modifications appears to be the much logical approach. Stress increases mineral and vitamin mobilization from tissues and their excretion. Effect of some minerals and vitamin supplements such as chromium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 61 publications
3
35
0
Order By: Relevance
“…Decreased proportions of C14:0, C16:0 and C18:0 and increased proportions of C16:1 and C18:2n‐6 were also observed in the PGZ plus CrMet group. Collectively, these changes could be attributed to the fatty deposit capacity of PGZ and the oxidation resistance of CrMet …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased proportions of C14:0, C16:0 and C18:0 and increased proportions of C16:1 and C18:2n‐6 were also observed in the PGZ plus CrMet group. Collectively, these changes could be attributed to the fatty deposit capacity of PGZ and the oxidation resistance of CrMet …”
Section: Discussionmentioning
confidence: 99%
“…Following increases in IMF content, lipid oxidation is an adverse factor that damages meat quality . Chromium methionine (CrMet), in particular, has been considered one of the best options for protecting the increased IMF content from oxidation . However, studies on the antioxidant effect of CrMet have mainly focused on mammals .…”
Section: Introductionmentioning
confidence: 99%
“…Khan et al (2014) found that adding Cr to broiler diets increased lymphoid organ weight (spleen). The combined effects of Cr and vitamin C in broiler diets under HS improved quality and carcass traits (Haq et al, 2016). Broilers fed supplemental Cr 500, 1000, and 1500 ppb under summer conditions showed significantly improved carcass yield and reduced abdominal fat (Toghyani et al, 2006).…”
Section: Carcass Traitsmentioning
confidence: 99%
“…In addition, the positive impacts of Cr on growth performance and blood parameters have been connected to chromodulins ability to improve the sensitivity of tissue receptors to insulin (Vincent 2000). Cr participation in the metabolism of carbohydrate including glucose (uptake and utilization) for lipogenesis and glycogen production (Haq et al 2016).…”
Section: Serum Biochemistry Indicesmentioning
confidence: 99%